A new approach of selecting real input ground motions for seismic design The most unfavourable real seismic design ground motions. - Zhai, Chang-Hai (Earthquake engineering & structural dynamics.)
This paper presents a new way of selecting real input ground motions for seismic design and analysis of structures based on a comprehensive method for estimating the damage potential of ground motions, which takes into consideration of various ground motion parameters and structural seismic damage criteria in terms of strength, deformation, hysteretic energy and dual damage of Park & Ang damage index. The proposed comprehensive method fully involves the effects of the intensity, frequency content and duration of ground motions and the dynamic characteristics of structures. Then, the concept of the most unfavourable real seismic design ground motion is introduced. Based on the concept, the most unfavourable real seismic design ground motions for rock, stiff soil, medium soil and soft soil site conditions are selected in terms of three typical period ranges of structures. The selected real strong motion records are suitable for seismic analysis of important structures whose failure or collapse will be avoided at a higher level of confidence during the strong earthquake, as they can cause the greatest damage to structures and thereby result in the highest damage potential from an extended real ground motion database for a given site. In addition, this paper also presents the real input design ground motions with medium damage potential, which can be used for the seismic analysis of structures located at the area with low and moderate seismicity. The most unfavourable real seismic design ground motions are verified by analysing the seismic response of structures. It is concluded that the most unfavourable real seismic design ground motion approach can select the real ground motions that can result in the highest damage potential for a given structure and site condition, and the real ground motions can be mainly used for structures whose failure or collapse will be avoided at a higher level of confidence during the strong earthquake.